A Comprehensive Review: Corporate social responsibility, government and civil society - Ali Basyah, Nazaruddin (MIMBAR : Jurnal Sosial dan Pembangunan, 2024)
This article explores the relationship between corporate social responsibility (CSR) and the roles played by governments and civil society in shaping and encouraging CSR. The article begins by examining how CSR is related to specific patterns of business–government–civil society relations. Two basic models are explored: the dichotomous view that suggests CSR and government are mutually exclusive, and the view that CSR is the relationship between market actors and governments. The article also investigates recent changes in business–government–civil society relations, which have contributed to the growth and development of CSR. Finally, the article examines the ways in which governments have promoted CSR and how responsible public and private policies are interconnected. The article highlights the fact that the relationship between business, government, and civil society has a significant impact on the scope and nature of CSR.